Cooperação penal transfronteiriça nos processos de integração: perspectivas de um novo paradigma para a preservação do meio ambiente - Almeida, Carla Dolores Castro de (2007)
This dissertation aims to approach the penal cooperation under the view of the environmental criminality. This, in turn, represents one of the multi-face variations of the modern criminality. The new criminality has brought in its essence the breakage of several paradigms which rule the penal right, resulting from that, the high relevance of the deepening in the theme. Because of the fact that the most devastating form of environmental criminality has as its principal characteristic being international, that is, the harming effects surpass the frontiers it becomes mandatory the treatment of this problem via cooperation among countries. From this statement, an analysis of the mechanisms existing in the European Union and in the Mercosul will occur to make effective the above mentioned cooperation. The present dissertation, according to the chosen approach for the theme, in the first chapter is about the international penal cooperation and focus the deepening in the study of penal cooperation in the European Unit and in Mercosul; In the second chapter it is approached, at first, the controversy about the criminalization of conducts which harm the environment from the statement that it is a fundamental human right. Still, in the second chapter, it is about the cooperation on environmental crime in Mercosul and in the European Unit and, finally, a country s legal diploma concerning to the environmental crime is made legal in the Law 9605/98 with emphasis in the chapter VII about the International Cooperation for the Preservation of the Environment.